A Comparison of Heparin Potency Estimates Obtained by Activated Partial Thromboplastin Time and British Pharmacopoeial Assays - Merton, R E; Curtis, A D; Thomas, D P (Thrombosis and Haemostasis, 1985)
Heparin samples from five manufacturers were assayed by the revised British Pharmacopoeia (BP) heparin assay and the results compared with those obtained using the activated partial thromboplastin time (APTT) assay. The United States Pharmacopeia (USP) reference heparin preparation and the 4th International Standard (IS) for heparin were also assayed by the two methods relative to the 3rd IS. The results obtained by the revised BP assay were in close agreement with those obtained by the APTT assay for all the heparins that were tested. The assays revealed that there is at least a 10% discrepancy between the International Unit for heparin and the USP unit.
Keywords: In vitro heparin assays; APTT; BP assay